ANALISIS DAMPAK SEKTOR INDUSTRI MANUFAKTUR, KEMISKINAN DAN BELANJA PEMERINTAH BIDANG LINGKUNGAN TERHADAP KUALITAS AIR DI INDONESIA - Azanul Akbar Lubis (Quantitative Economics Journal, 2015)
Manufacturing sector is one of the sectors that contribute to economic growth in Indonesia. Results of these contributions is the changing structure of the Indonesian economy from agriculture to the industrial sector. And poverty in Indonesia which is one indicator of well‐being in an area tend to be in 2000 to 2010 has a pattern that tends to decline, although not very significant. Of 2 (two) variables, namely the Manufacturing Sector and Poverty, the author tries to determine the impact of variables on water quality in Indonesia, by adding variable Expenditures Environmental Affairs as variables that also impact the water quality in Indonesia. Manufacturing Sector GDP, the number of poor, Regional Budget (APBD) Environmental Field, each is used as a proxy for the manufacturing sector, poverty and Environment Sector Government expenditure. The data is compiled based on 28 provinces in Indonesia in 2009, 2010 and 2011. The results obtained showed that the industrial sector and poverty have a negative impact on water quality while Government Expenditure Environment Sector positive effect on water quality in Indonesia.